Surviving climate chaos by strengthening communities and ecosystems - Caldecott, Julian 1956- (Cambridge University Press, 2021)
Surviving climate chaos needs communities and ecosystems able to cope with near-random impacts. Their strength depends upon their integrity, so preserving and restoring this is essential. Total climate breakdown might be postponed by extreme efforts to conserve carbon and recapture pollutants, but climate chaos everywhere is now inevitable. Adaptation efforts by Paris Agreement countries are converging on community-based and ecosystem-based strategies, and case studies in Bolivia, Nepal and Tanzania confirm that these are the best ways forward. But success depends on local empowerment through forums, ecosystem tenure security and environmental education. When replicated, networked and shielded by governments, they can strengthen societies against climate chaos while achieving sustainable development. These vital messages are highlighted for all those who seek or have already found a role in promoting adaptation: for students, researchers and teachers, government officials and aid professionals, and for everyone who is now living under threat of climate chaos